Effects of supplementary nutrient in an aquaponic system for production of ornamental red tilapia (Oreochromis Sp.) and lettuce (Lactuca sativa var longifolia) - Rafiee, Gh. R.; Saad, Che Roos; Kamarudin, Mohd Salleh; Ismail, Mohd Razi; Sijam, K. (Iranian Ornamental Fish Society, 2018)
Effects of supplementary nutrient in the production of red tilapia (Oreochromis sp) and Lettuce (Lactuca sativa var longifolia) evaluated in a representative water recirculating aquaculture system. The nutrient solution supplemented was 25% level of (L25) nutrient solution as medium used for aquaponic production of lettuce in the NFT system (based on cooper’s formula). Thus, a completely randomized experimental design conducted with two treatments in triplicates (Pl25 and PL0). Six black rectangular tanks (114 x 86 x 100cm) used as fish culture tanks and each one equipped with three hydroponic troughs. Each tank filled with 640 L of water and aerated continuously with two circular air stones (3 L min-1) during the experiment. The system was efficiently able to remove high rate of total ammonia -nitrogen (TAN) excreted by fish during the experiment. The fish attained marketable size (200g) during a 110 –day period. Nutrient supply had not significant effects (p>0.05) on growth of fish during experimental period. The yields (Biomass/tank) of fish in treatments PL25 and Pl0 were 9.97 and 9.26 kg / tank, respectively. Three times cultivation and harvest of lettuce carried out during the experimental period. At the first harvest, the yield (mean wet weight) of lettuce showed significant (p<0.05) differences between treatments, 1437g and 85 g in treatments PL25 and Pl0, respectively. In the second and third lettuce harvests, the yield of lettuce did not show any significant differences (p>0.05) and averaged 2112 and 1419 (Second harvest) and 1173 and 807 (Third harvest) for treatments PL25 and PL0, respectively. It was recorded that red tilapia could tolerate 25% of nutrient solution, used for aquaponic production of lettuce, and introduction of nutrient solution to the culture system is necessary to get higher yield of lettuce at initiation of culture system.